Assessment of the Shelf life of Quail Egg Pickle - Deepa Menon (Department of Poultry Science, College of Veterinary and Animal Sciences, 2001)
An investigation was carried out at the Department of Poultry Science, College of Veterinary and Animal Sciences, Mannuthy to assess the shelf life of vinegar, oil based quail egg